Criminal Confrontation of Illicit Banking Operations:A Case Study of the Offense of Terrorist Financing and Failure to Report Suspicious Financial Activities - Abdul Kareem Jasim, Researcher. Marwah; Hammad Hamid , Prof.Dr. Hassan (Basra studies journal, 2025)
The offense of terrorist financing within the banking sector constitutes a serious threat to the integrity and security of national and international financial systems. Terrorist groups often exploit banking institutions to move illicit funds and obtain the financial resources necessary to carry out their activities. They employ sophisticated concealment methods aimed at obscuring the true source of the funds، such as using shell companies، conducting complex financial transfers، or manipulating banking systems to give the funds an appearance of legitimacy. The gravity of this offense lies in its close connection to transnational criminal networks and its ability to blend seamlessly into routine banking operations. In this context، the offense of failing to report suspicious financial transactions has emerged as an independent and significant crime. It occurs when financial institutions or their employees deliberately—or negligently—fail to report transactions that raise suspicion. Such failure represents a breach of legal and regulatory duties، facilitates the commission of money laundering and terrorist financing offenses، and undermines the effectiveness of the national framework designed to combat these activities.